The Algorithmic Gaze: Surveillance, Privacy, and the Future of Social Interaction - Dr. Farhat Basir (Research Journal of Psychology, 2023)
The pervasive presence of algorithms in our online interactions has created a new form of panoptic surveillance – the algorithmic gaze. This article examines the implications of this gaze on individual privacy, the nature of social interaction, and the potential erosion of agency and autonomy in the digital age. We explore the mechanisms of algorithmic surveillance, the ethical concerns it raises, and potential avenues for navigating its complexities and mitigating its harms.